REGULATION OF BUSINESS CONGLOMERATES IN CHILE: A NORMATIVE AND DOCTRINAL DESCRIPTION - Donetch Ulloa, Maria Cristina; Mendez Romero, Ricardo Antonio; Haro Paillán, Nicolás Alejandro (My University, 2025)
The current economic situation in Chile shows that business conglomerates, also called holding companies, represent a strong basis in the country's economic development. These groups of companies imply links in ownership and management, although each associated company has its own legal personality. Thus, these different legally independent companies act administratively under the strategic direction of a central entity, called the parent company. The objectives of the research refer to: [1] conceptualize business conglomerates in Chile; [2] to identify and describe the different types of links that define the precept of business conglomerate in Chile; [3] Describe and analyze the economic, financial, labor and tax regulations applicable to business conglomerates in Chile. This study is defined as qualitative, descriptive, and situational research. The methodology applied is structured through a non-experimental design, from a qualitative perspective and the techniques of documentary and content analysis are applied. The results obtained show that the legal figure of corporations is the basis of the structuring and relationship of these groups of economic concentration, that Chilean legal norms strongly condition the actions of business conglomerates, but that they can act freely in their corporate aspects, to the extent that their acts are within the current legal framework. The main conclusions indicate that a business conglomerate exists when a group of companies have a corporate structure of parent company and subordinate companies, with common purposes and business management unity. In tax matters, the regulation recognizes Tax Planning as valid, but the auditing entity can qualify the actions of companies as abusive or simulation acts. In the financial sphere, the prohibited acts are operations between companies and related persons and what is required is transparency in the delivery of corporate information. In the economic sphere, FNA not only acts according to the unlawful acts explicit in the rules but also has the power to qualify as contrary to free competition, any strategy of a conglomerate that could potentially produce negative consequences in the markets.